2017
DOI: 10.1088/1361-6528/aa66a4
|View full text |Cite
|
Sign up to set email alerts
|

In-situthermal annealing of on-membrane silicon-on-insulator semiconductor-based devices after high gamma dose irradiation

Abstract: In this paper, we investigate the recovery of some semiconductor-based components, such as N/P-type field-effect transistors (FETs) and a complementary metal-oxide-semiconductor (CMOS) inverter, after being exposed to a high total dose of gamma ray radiation. The employed method consists mainly of a rapid, low power and in situ annealing mitigation technique by silicon-on-insulator micro-hotplates. Due to the ionizing effect of the gamma irradiation, the threshold voltages showed an average shift of -580 mV fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…This annealing temperature is quite low compared with that of the Si‐based ICs, which is over 300 °C with comparable time. [ 27 ] The annealing‐induced recovery of a typical MoS 2 PSE‐inverter is similar to that of a single MoS 2 PSE‐FET, in which V tr exhibits a positive shift after irradiation and a partial recovery after annealing.…”
Section: Damage Recovery Via Annealingmentioning
confidence: 94%
See 1 more Smart Citation
“…This annealing temperature is quite low compared with that of the Si‐based ICs, which is over 300 °C with comparable time. [ 27 ] The annealing‐induced recovery of a typical MoS 2 PSE‐inverter is similar to that of a single MoS 2 PSE‐FET, in which V tr exhibits a positive shift after irradiation and a partial recovery after annealing.…”
Section: Damage Recovery Via Annealingmentioning
confidence: 94%
“…[25] Nevertheless, further irradiation will still lead to failure of MoS 2 PSE devices. Such "failure" is defined according to standards of commercial radiation-hardened Si-based ICs, as the change of threshold voltage ΔV th or ΔV tr > 0.3 V. [26] For Sibased ICs, thermal annealing processes of about 300-900 °C for 4-30 min, [27,28] or around 100 °C for several hours have been employed to partially recover the initial threshold voltage. [29] In PSE devices, we found that a much milder condition could induce a large recovery effect.…”
Section: Damage Recovery Via Annealingmentioning
confidence: 99%
“…the thermally activated dopant diffusion or the degradation of the metal layers, a wide variety of reliability issues related to the different coefficients of thermal expansion for System-in-Package (SiP) technology, and by the bulky equipments and their high power consumption needed to achieve the thermal treatment. Recent works improved a revolutionary success by improving an in situ low power total recovery of semiconductor based devices after high gamma dose irradiation [6]. In this work, our interest is rather focusing on the proton radiation, by studying the electrical characteristics of SOI electronic components embedded in a 5 µm-thick microhotplate membrane and analyzing the degradations that appeared after proton irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the abovementioned recovery method in a unit transistor level, other groups suggested recovery methods utilizing an embedded heater module, which was intercalated into a package 913 , i.e., interior heater. In terms of layout efficiency, the recovery method in the package level is more preferred than that in the transistor level.…”
Section: Introductionmentioning
confidence: 99%
“…But, the former still accompanies with extra fabrication of heater module including temperature sensor and its assembly and is not a cost-effective approach, either. In addition, it demanded relatively high power for heating and the induced heat distribution was not uniform 9 . Hence longer recovery time was required.…”
Section: Introductionmentioning
confidence: 99%